A View of Declining of Christianity in America through “Avatar”: A Semiotic Approach - Sriastuti, Anna (TEKNOSASTIK, 2024)
This study delves into the pivotal role of religion in shaping the American narrative, emphasizing the waning influence of Christianity. Originating from the historical context of the Puritans' break from the Church of England to purify their faith, Christianity has experienced significant shifts in prevalence among Americans. While it was once a ubiquitous identity, recent trends indicate a decline, with approximately two-thirds of adults now identifying as Christians. This evolving religious landscape has become a matter of concern for Americans, influencing various literary works. Notably, the Avatar film series, encompassing Avatar and Avatar: The Way of Water, subtly addresses issues of religious beliefs. Despite the less overt exploration of religious themes, the presence of a Great Mother figure in the narratives suggests a persistent inclination toward supernatural beliefs. Employing a descriptive qualitative method and specifically utilizing conceptual and associative meanings in the semiotic approach, this study analyzes the nuanced portrayal of Christianity's decline in America within the context of the Avatar film series.